Insights on Current Strategies to Decolonize the Gut from Multidrug-Resistant Bacteria: Pros and Cons - Natalia Roson-Calero; Clara Ballesté-Delpierre; Javier Fernández; Jordi Vila (MDPI AG, 2023)
In the last decades, we have witnessed a steady increase in infections caused by multidrug-resistant (MDR) bacteria. These infections are associated with higher morbidity and mortality. Several interventions should be taken to reduce the emergence and spread of MDR bacteria. The eradication of resistant pathogens colonizing specific human body sites that would likely cause further infection in other sites is one of the most conventional strategies. The objective of this narrative mini-review is to compile and discuss different strategies for the eradication of MDR bacteria from gut microbiota. Here, we analyse the prevalence of MDR bacteria in the community and the hospital and the clinical impact of gut microbiota colonisation with MDR bacteria. Then, several strategies to eliminate MDR bacteria from gut microbiota are described and include: (i) selective decontamination of the digestive tract (SDD) using a cocktail of antibiotics; (ii) the use of pre and probiotics; (iii) fecal microbiota transplantation; (iv) the use of specific phages; (v) engineered CRISPR-Cas Systems. This review intends to provide a state-of-the-art of the most relevant strategies to eradicate MDR bacteria from gut microbiota currently being investigated.